1999
DOI: 10.4319/lo.1999.44.7.1730
|View full text |Cite
|
Sign up to set email alerts
|

Rates and routes of trace element uptake in zebra mussels

Abstract: The zebra mussel, Dreissena polymorpha, a nonindigenous invasive species, is now widespread throughout the eastern half of North America. Because zebra mussels are ubiquitous and because they effectively filter particulate matter out of suspension, the cycling and residence times of particle-reactive metals will likely be affected in waters with zebra mussels. This study describes experiments designed to assess the possibility of using this species as a bioindicator of metals in ambient freshwater environments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
74
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 44 publications
13
74
0
1
Order By: Relevance
“…3). These results confirm the ability of zebra mussels to actively regulate metals and to excrete them from their tissues (Roditi and Fisher, 1999;Bourgeault et al, 2011). Besides, these results highlight that the dredging operation had a transient effect on caged mussels when considering both metal bioaccumulation and mortality.…”
Section: Impact Of Dredging On Metal Bioaccumulationsupporting
confidence: 76%
“…3). These results confirm the ability of zebra mussels to actively regulate metals and to excrete them from their tissues (Roditi and Fisher, 1999;Bourgeault et al, 2011). Besides, these results highlight that the dredging operation had a transient effect on caged mussels when considering both metal bioaccumulation and mortality.…”
Section: Impact Of Dredging On Metal Bioaccumulationsupporting
confidence: 76%
“…5 to estimate the biological half-life (t ½ ) of Cd, which is ϳ1 week for the whole insect and its constituent parts (Table 1). The value of the Cd loss rate constant k E (Table 1) for whole H. limbata (0.09 d Ϫ1 ) is similar to, but somewhat lower than, those reported for copepods (0.1-1.3 d Ϫ1 ) (Wang and Fisher 1998;Xu et al 2001) and higher than those reported for bivalves (0.01-0.03 d Ϫ1 ) (Roditi and Fisher 1999;Chong and Wang 2001) and gastropods (0.001-0.005 d Ϫ1 ) (Wang and Ke 2002). The values of the loss rate constants for the gut and body portions that we measured in our field study (0.11 and 0.13 d Ϫ1 , respectively) are similar to those reported from a laboratory study on Hexagenia rigida (0.10 and 0.09 d…”
Section: Termmentioning
confidence: 75%
“…The assimilation efficiencies of Cd associated with algae (70~90%) and sediment (40~65%) in C. fluminea were generally higher than the respective AEs in bivalves including cases involving various sediment-dwelling clams (Macoma balthica, Potamocorbula amurensis and Ruditapes philippinarum) and mussels (Dreissena polymorpha, M. edulis and Perna viridis) from previous studies (Roditi and Fisher 1999;Lee and Luoma 1998;Chong and Wang 2000;Ke and Wang 2001).…”
Section: Assimilation Of Ingested Metalsmentioning
confidence: 94%
“…A relatively small fraction of metals was present in the form of cytosolic form in algalpoor suspended particles and sediments (Lee and Luoma 1998). Similarly, the nutritional quality of food might influence the AEs of metals as well as the AE of carbon in the food (Roditi and Fisher 1999).…”
Section: Assimilation Of Ingested Metalsmentioning
confidence: 99%